UV: Friend or Foe? - Santos, A.; Pontes, C.; Chaves, E.; Oliveira, F.; Ribeiro, M.; Abreu, R.; Visinho, T. (Open Schools Journal for Open Science, 2020)
For about four months, in the 2018-2019 school year, students from Escola Secundária Jaime Moniz were involved in the project “UV-friendly or enemy?”. The project went through various activities that promoted interdisciplinarity between the disciplines of Physics, Chemistry, Biology and Geology, and established contacts with their community. They also had the chance to conduct surveys and share the responses obtained on the Goballab platform, gaining awareness of the relevance of the problems associated with sun exposure at local and global levels. In the end, each group of students from each of the classes, created a product to present to the educational community, raising awareness of the problem studied. The products created were: posters, leaflets, games and a song (original lyrics and music) warning about the dangers and benefits of ultraviolet radiation for human health and the use of sunscreens.